We Can’t Stop the Hackers. - SANGER, DAVID E. (New York Times, 2018)
The article highlights the concerns of finance ministries and bankers across the world about North Koreans or the Russians abilities of huge cyber-attacks, as of June 2018. Topics discussed include the cyber-attacks of 2017 that temporarily crippled the British health care system and the other devastated Ukraine before rippling across the world; and cyber attackers believe that no risk that the U.S. or any other power would retaliate with significant sanctions.